The Effect of Hedonic Shopping Value and Shopping Lifestyle on the Impulse Buying in Online Shops (case study: Albadar 6 Gang Community) - Sri Wahyuni; Wan Suryani; Wan Rizca Amelia (Universitas Medan Area, 2022)
This study was conducted with the aim of knowing the effect of hedonic shopping value and shopping lifestyle on the impulse buying of Albadar 6 gang community. This type of research is quantitative descriptive, which is a study that aims to explain an empirical phenomenon accompanied by statistical data, characteristics and relationships between variables using techniques. data collection using questionnaires and literature study. Data collection in this study was carried out by distributing questionnaires using a Likert scale. The sample in this study was the community of Gang Albadar 6, amounting to 78 respondents using the Slovin formula. The method used in data collection is purposive sampling. The analysis technique uses multiple linear regression analysis with the help of SPSS 25 program. The results of this study indicate that the two independent variables, namely hedonic shopping value and shopping lifestyle, affect impulse buying. The value of R Square equation of 0.595 means that the impulsive buying variable (dependent) which can be explained by the hedonic shopping value and shopping lifestyle (independent) variables in this study is 59.5% while 40.5% is influenced by other variables not explained by the this study.